COMPARISON OF TOTAL PRESSURE FLUCTUATIONS IN STEAM TURBINE STAGES WITH DIFFERENT DEGREE OF REACTION - Tomáš Jelínek; Martin Němec; Petr Milčák (Acta Polytechnica CTU Proceedings)
The contribution deals with analysis of unsteady pressure measurement in one and half axial turbine stages. The measurement was performed in VZLU air test turbine. Two stages geometries with different degree of reaction were tested in this work. Comparison of unsteady flow field behaviours is discussed.